(untitled) (New Jersey, 2003)
This book contains 36 articles covering most of the topics in the rapidly developing areas of meshfree methods and extended finite element methods (X-FEM). These topics include domain discretization, boundary discretization, combined domain/boundary discretization, meshfree particle methods, collocation methods, X-FEM, etc.
Keywords: Meshfree methods (Numerical analysis),Finite element method,Phương pháp Meshfree (Giải tích số),Phương pháp phần tử hữu hạn